Lack of association between IL-1 and IL-6 gene polymorphisms and myocardial infarction in Turkish population - (:unkn) unknown (WILEY, 2011)
P>Inflammation and genetics play a key role in the pathogenesis of atherosclerosis and its clinical result myocardial infarction (MI). Proinflammatory cytokines, IL-1 and IL-6, have been shown to play essential roles in developmental stages of coronary artery plaque formation. The aim of this study was to determine the association between IL-1 [IL-1RN, IL-1 beta (-511, +3953)], IL-6 [-174, -572, -597] gene polymorphisms and MI in Turkish population. A total of 402 people were participated; 235 healthy control subjects and 167 MI patients (MI < 40, n: 72; MI > 40, n: 95). Polymerase chain reaction (PCR) was used to determine the genotype of IL-1RN, whereas the genotypes of IL-1 beta (-511, +3953) and IL-6 (-174, -572, -597) were determined using PCR followed with restriction digestion analysis. There was no significant difference between MI and controls for IL-1RN, IL-1 beta-511, +3953 (P: 0.875, 0.608, 0.442) and IL-6 -174, -572, -597 (P: 0.977, 0.632, 0.584) gene polymorphisms. Lack of association was observed between MI at younger age (MI < 40) and either IL-1RN VNTR, IL-1 beta-511, +3953 (P: 0.878, 0.732, 0.978) or IL-6 -174, -572, -597 (P: 0.313, 0.654, 0.552) gene polymorphisms. This study demonstrated that there was not any association between IL-1, IL-6 gene variants and MI in Turkish population. In addition, IL-1 and IL-6 gene polymorphisms did not affect MI at younger age (MI < 40) or older age (MI > 40). Thus, IL-1 and IL-6 single nucleotide polymorphisms may not be a risk factor for susceptibility to MI in Turkish population.
Keywords: CORONARY-ARTERY-DISEASE; RECEPTOR ANTAGONIST GENE; SMOOTH-MUSCLE-CELLS; C-REACTIVE PROTEIN; INTERLEUKIN-1 RECEPTOR; PROMOTER POLYMORPHISMS; NO ASSOCIATION; MONONUCLEAR-CELLS; PLASMA-LEVELS; RISK